Efek Koefisien Transmisi akibat Variasi Wave Stepness pada Hexagonal Artificial Reef - Wirayuhanto, Harish; Armono, Haryo Dwito; Ridlwan, Asfafur; Febrianto, Try (Rekayasa, 2021)
Waves that move towards the coast have an energy level that corresponds to the magnitude of the generating force. Waves with high energy intensity are dominantly destructive when they hit the coastal area. In order to reduce the destructive effect of waves, coastal protection structures are needed to dampen the wave energy. Artificial coral reef (artificial reef) is one type of structure that can reduce wave energy. Besides functioning as an artificial reef for marine ecosystem biota, but also as a submerged breakwater structure. This study was conducted to determine the relationship between wave stepness and the transmission coefficient produced by hexagonal artificial reefs with a model scale of 1:10. The test is carried out using regular waves with a range of H/gT2 values between 0.0007 – 0.006. The results of research conducted at the Marine Energy Laboratory of the Department of Marine Engineering, FTK ITS, show that an increase in the value of wave steepness correlates with an increase in the value of the transmission coefficient (Kt) for all tests and configurations. The 1D structure configuration has a lower transmission coefficient (Kt) than the 0D structure configuration for each variation of the test wave.